Identification and Functional Characterization of Two Intronic NIPBL Mutations in Two Patients with Cornelia de Lange Syndrome. (26th January 2016) - Teresa-Rodrigo, María E.; Eckhold, Juliane; Puisac, Beatriz; Pozojevic, Jelena; Parenti, Ilaria; Baquero-Montoya, Carolina; Gil-Rodríguez, María C.; Braunholz, Diana; Dalski, Andreas; Hernández-Marcos, María; Ayerza, Ariadna; Bernal, María L.; et al.
Abstract : Cornelia de Lange syndrome (CdLS) is a rare genetically heterogeneous disorder with a high phenotypic variability including mental retardation, developmental delay, and limb malformations. The genetic causes in about 30% of patients with CdLS are still unknown. We report on the functional characterization of two intronic NIPBL mutations in two patients with CdLS that do not affect a conserved splice-donor or acceptor site. Interestingly, mRNA analyses showed aberrantly spliced transcripts missing exon 28 or 37, suggesting the loss of the branch site by the c.5329-15A>G transition and a disruption of the polypyrimidine by the c.6344del(-13)_(-8) deletion. While the loss of exon 28 retains the reading frame of the NIBPL transcript resulting in a shortened protein, the loss of exon 37 shifts the reading frame with the consequence of a premature stop of translation. Subsequent quantitative PCR analysis demonstrated a 30% decrease of the total NIPBL mRNA levels associated with the frameshift transcript. Consistent with our results, this patient shows a more severe phenotype compared to the patient with the aberrant transcript that retains its reading frame. Thus, intronic variants identified by sequencing analysis in CdLS diagnostics should carefully be examined before excluding them as nonrelevant to disease.